2015
DOI: 10.5194/nhessd-3-2493-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New estimates of potential impacts of sea level rise and coastal floods in Poland

Abstract: Abstract. Polish coastal zone is thought to be of the most exposed to sea level rise in Europe. With climate change expected to raise mean sea levels between 26 and 200 cm by the end of the century, and storms increasing in severity, accurate estimates of those phenomena are needed. Recent advances in quality and availability of spatial data in Poland made in possible to revisit previous estimates. Up-to-date detailed information on land use, population and buildings were used to calculate inundation risk at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
1
11
0
2
Order By: Relevance
“…In recent decades, the highest absolute amplitude of sea level changes in the study area was recorded during year 1984 (2.79 m), whereas the most extreme storm surge occurred in November 1995 (+1.61 m above mean) (Wolski et al, 2013). However, extreme value analysis have shown that a 100year storm surge in the western part of the Polish coast could reach +1.71 m above mean, and a 500-year event would exceed 2 m (Paprotny and Terefenko, 2017). The highest recorded sea level in the timeframe of this study was 1.4 m and corresponds approximately to an event with a return period of 20 years.…”
Section: Study Areamentioning
confidence: 62%
“…In recent decades, the highest absolute amplitude of sea level changes in the study area was recorded during year 1984 (2.79 m), whereas the most extreme storm surge occurred in November 1995 (+1.61 m above mean) (Wolski et al, 2013). However, extreme value analysis have shown that a 100year storm surge in the western part of the Polish coast could reach +1.71 m above mean, and a 500-year event would exceed 2 m (Paprotny and Terefenko, 2017). The highest recorded sea level in the timeframe of this study was 1.4 m and corresponds approximately to an event with a return period of 20 years.…”
Section: Study Areamentioning
confidence: 62%
“…However, such results have to be interpreted with caution, especially considering changing adaptation and risk reduction capacity. In addition, future flood risk in coastal zones will increase due to the sea level rise (Paprotny and Terefenko, 2017). As projected by Vousdoukas et al (2018), taking into account both the socioeconomic pathways and climate change but in absence of further investments in adaptation, annual damage by coastal flood in Europe will increase from current 1.25 € billion to 93 -961€ billion in the end of 21st century, and current 0.1 million exposed population will reach 1.52 -3.65 million.…”
Section: Figmentioning
confidence: 99%
“…In addition, future flood risk in coastal zones will increase due to the sea level rise (Paprotny and Terefenko, 2017). Taking into account both the socioeconomic pathways and climate change but in absence of further investments in adaptation, Vousdoukas et al (2018) projected the annual damage caused by coastal flooding in Europe to increase from the current EUR 1.25 billion to EUR 93-961 billion by the end of the 21st century, and the exposed population to increase from the current level of 0.1 million to 1.52-3.65 million.…”
Section: Introductionmentioning
confidence: 99%